Soil-soil solution distribution coefficient of soil organic matter is a key factor for that of radioiodide in surface and subsurface soils. (April 2017) - Unno, Yusuke; Tsukada, Hirofumi; Takeda, Akira; Takaku, Yuichi; Hisamatsu, Shun'ichi
Abstract: We investigated the vertical distribution of the soil–soil-solution distribution coefficients ( K d ) of 125 I, 137 Cs, and 85 Sr in organic-rich surface soil and organic-poor subsurface soil of a pasture and an urban forest near a spent-nuclear-fuel reprocessing plant in Rokkasho, Japan. K d of 137 Cs was highly correlated with water-extractable K + . K d of 85 Sr was highly correlated with water-extractable Ca 2+ and SOC. K d of 125 I − was low in organic-rich surface soil, high slightly below the surface, and lowest in the deepest soil. This kinked distribution pattern differed from the gradual decrease of the other radionuclides. The thickness of the high- 125 I − K d middle layer ( i.e., with high radioiodide retention ability) differed between sites. K d of 125 I − was significantly correlated with K d of soil organic carbon. Our results also showed that the layer thickness is controlled by the ratio of K d -OC between surface and subsurface soils. This finding suggests that the addition of SOC might prevent further radioiodide migration down the soil profile. As far as we know, this is the first report to show a strong correlation of a soil characteristic with K d of 125 I − . Further study is needed to clarify how radioiodide is retained and migrates in soil. Highlights: Distribution coefficients ( K d ) of 125 I −, 137 Cs, and 85 Sr were measured. K d of 125 I − showed similar trend to K d of soil organic C. K d of 125 I − was highest just below the surface. How this middle layer retains 125 I − must be determined.